Humans, Stocks, and Morals: Starbucks Ethical Dilemma in Global Boycotts, Corporate Accountability, and Islamic Legal Perspectives - Salsabila Rudini, Khansa; Purwanti, Lilik (CITACONOMIA : Economic and Business Studies, 2025)
This study analyzes the ethical dilemma faced by Starbucks stakeholders in the global boycott crisis resulting from the Israel-Palestine conflict, integrating an Islamic legal perspective based on Imam Al-Thabari's interpretation of QS. At-Taubah (9) verse 5 regarding the legitimacy of economic boycotts, and its impact on multidimensional corporate accountability. The decline in SBUX shares from USD 107.21 to USD 93.89, with a market value loss of USD 12 billion, demonstrates the concrete financial impact of the company's social-ethical legitimacy crisis. The analysis reveals a substantial gap between reported financial accountability and the social-ethical accountability that should be accounted for to all stakeholders in the context of global moral values and religiosity. The multistakeholder ethical dilemma requires the integration of humanistic accounting perspectives into a more comprehensive corporate accountability framework, accompanied by a deep understanding of the Islamic legal doctrines underlying the Muslim consumer boycott movement. The findings reinforce legitimacy theory by demonstrating the financial impact of global value conflicts on the stability of multinational companies, while acknowledging spirituality and religious compliance as key drivers of consumer behavior in an era of ethical awareness integrated with religious values.